Diffraction of sound waves by a lined cylindrical cavity - (:unkn) unknown (SAGE PUBLICATIONS INC, 2020)
In this paper, diffraction of sound waves through a lined cavity is analyzed rigorously. The inner-outer surfaces of the cavity and the base of the cavity are coated with three different absorbing linings. By using the Fourier transform technique in conjunction with the Mode-Matching method, the related boundary value problem is formulated as a Wiener-Hopf equation. In the solution, two infinite sets of unknown coefficients are involved that satisfy two infinite systems of linear algebraic equations. Numerical solution of this system is obtained for various values of the parameters of the problem. The graphical results are also presented which show that how efficiently the sound diffraction can be reduced by selection of problem parameters.
Keywords: Wiener-Hopf; Fourier transform; cavity; Mode Matching; absorbing lining; RADIATION; SCATTERING; IMPEDANCE; DUCT